ON THE EVOLUTION OF WOLF-RAYET STARS IN CLOSE BINARY SYSTEMS - Cherepashchuk, A. M.; Karetnikov, V. G. (Одеські астрономічні публікації, 2017)
The statistical study of the mass ratios of the components and eccentricities of close binary systems was made. Relations between these characteristics are obtained. Results of the analysis allows to conclude that at least 70 of all known WR+O binary systems (with orbital period P < 20d) where formed as a result of mass transfer in massive close binary systems. Therefore, mass transfer through Roche lobe overflowing in massive close binary systems is an important mechanism of evolution in these interacting binaries.